PENGARUH KESADARAN WAJIB PAJAK DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI MELALUI PENERAPAN SISTEM ADMINISTRASI PERPAJAKAN - Yuliadi Yuliadi (Politeknik Caltex Riau, 2018)
This study aims to examine the effect of taxpayer awareness and fiscal services on taxpayer compliance with the tax administration system as an intervening variable. This study uses quantitative methods and uses the SPSS program on testing the validity and reliability of the research instrument. The variables analyzed in this study were taxpayer awareness and fiscal services as independent variables, the tax administration system as a taxpayer intervention and compliance variable as the dependent variable. This study uses a sample of 100 respondents who are individual taxpayers registered at the Batam Primary Tax Service Office in the city of Batam. This study uses purposive sampling technique and uses primary data with a questionnaire. The results of the study showed that there was a significant influence of Taxpayer Awareness, Fiscus Service, and Tax Administration System on Taxpayer Compliance in the amount of 43.4%, 8.6% and 22.2%. While indirectly there is no significant effect between the variables of Taxpayer Awareness and Fiscal Services on performance through the Tax Administration System. Indirect influence is given at 11.14% and 0.244%.